Didactics of specialized translation – Experiences and observations on student translation errors in the case of a wine-related document - Nadja Dobnik (Scripta Manent, 2019)
Languages for specific purposes and technical terminology are key to developing professional competencies in future translators. During their undergraduate translation studies at the Faculty of Arts in xxx, students work with a broad range of texts, reaching from general-purpose to specialized texts (from economics, law, tourism etc.). Previous experience shows that while inexperienced translators and students feel a great deal of apprehension and uncertainty when faced with demanding technical texts, they nevertheless translate them successfully, primarily because the fear of the text motivates them to conduct in-depth research and seek solutions carefully. On the other hand, with general informative texts, which they do not perceive as technically challenging, they often overlook technical and culture-specific items, leading to severe translation errors. In order to verify this presumption, we analysed the translations of select technical and culture-specific terms in the text “Caractéristiques des vins d’Alsace” (Characteristics of the wines of Alsace). We were interested to see whether students working with a text that provides general information on different types of wine would identify its technical and culture-specific terms, and what solutions they would use in their translations.